The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/1755-1315/1151/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Scenario of reducing carbon emission through shifting consumption of non-renewable energy to renewable energy in asia pacific 2023-2030

Abstract: This research is motivated by the high level of carbon emission due to the dominance of non-renewable energy consumption in the use of the energy mix. This study aims to fill the gaps in previous research to support global programs in reducing carbon emission by designing scenario through a shift in consumption of non-renewable energy (fuel oil) to renewable energy (biofuel oil) in the Asia Pacific for future periods, including 2023-2030. The basic foundation of this research is the result of panel regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
3
1
0
Order By: Relevance
“…This study's results are further confirmed by the findings of Mukhtarov et al (2023), who provide empirical evidence of a significantly negative long-term impact of renewable energy consumption on CO 2 emissions. Similar results can be found in earlier studies for different regions, such as (Rahman et al, 2022) in advanced economies, (Bhattacharya et al, 2017) in both advanced and developing nations, (Aimon et al, 2023)in the Asia-Pacific region, (Aziz et al, 2021) in MINT countries, and (Leitão et al, 2021) in BRICS nations. Additionally, the findings of Shaari et al (2020) strengthen the argument that the use of renewable energy can effectively reduce CO 2 emissions, especially in lower-middleincome countries.…”
Section: Renewable Energy Consumption and Co 2 Emissionssupporting
confidence: 90%
See 1 more Smart Citation
“…This study's results are further confirmed by the findings of Mukhtarov et al (2023), who provide empirical evidence of a significantly negative long-term impact of renewable energy consumption on CO 2 emissions. Similar results can be found in earlier studies for different regions, such as (Rahman et al, 2022) in advanced economies, (Bhattacharya et al, 2017) in both advanced and developing nations, (Aimon et al, 2023)in the Asia-Pacific region, (Aziz et al, 2021) in MINT countries, and (Leitão et al, 2021) in BRICS nations. Additionally, the findings of Shaari et al (2020) strengthen the argument that the use of renewable energy can effectively reduce CO 2 emissions, especially in lower-middleincome countries.…”
Section: Renewable Energy Consumption and Co 2 Emissionssupporting
confidence: 90%
“…Employing the pooled mean group method, their study found that renewable energy consumption generally leads to reductions in CO2 emissions in the short and long term. These findings are also corroborated by the study conducted by (Aimon et al, 2023) in the Asia-Pacific context. The key takeaway from their research is that renewable energy consumption and green economic growth can mitigate CO2 emissions, while non-renewable energy consumption tends to increase CO2 emissions.…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, reliance on renewable energy prevented resource depletion, mitigating the need for extraction and mining activities. This result was in line with [9,63,64], showing the crucial role of renewable energy consumption in mitigating environmental degradation.…”
Section: Analysis Of Environmental Degradationsupporting
confidence: 83%
“…On the other hand, the empirical phenomenon regarding this study, if traced from previous literature, shows that there are several main gaps in previous research, including Aimon et al (2023) conducted a literature review on the topic of modeling ecological relationships and POV from 4335 publications for the period 1981-2017, which found that ecological degradation and POV are interrelated and must be addressed simultaneously. In addition, Saputri & Pratama (2021) investigated financial inclusion, EG, and POV in eastern Indonesia during the 2010-2016 period by using bivariate vector autoregression, which found a strong relationship between these three variables.…”
Section: Research Phenomenonmentioning
confidence: 94%